Prevalence of subarachnoid haemorrhage among patients with cranial venous sinus thrombosis in the presence and absence of venous infarcts. Issue 5 (October 2018) - Azeemuddin, Muhammad; Awais, Muhammad; Mubarak, Fatima; Rehman, Abdul; Baloch, Noor Ul-Ain
Introduction: In patients with cranial venous sinus thrombosis, the occurrence of subarachnoid haemorrhage in association with haemorrhagic venous infarcts is a well described phenomenon. However, the presence of subarachnoid haemorrhage in patients with cranial venous sinus thrombosis in the absence of a haemorrhagic venous infarct is exceedingly rare. Methods: We retrospectively reviewed charts and scans of all patients who had cranial venous sinus thrombosis confirmed by magnetic resonance venography at our hospital between September 2004 and May 2015. The presence of subarachnoid haemorrhage was ascertained on fluid-attenuated inversion recovery, susceptibility-weighted imaging and/or unenhanced computed tomography scans by a single experienced neuroradiologist. Statistical analysis was performed using the Statistical Package for Social Sciences version 20. Differences in the proportion of haemorrhagic venous infarcts among patients with subarachnoid haemorrhage versus those without subarachnoid haemorrhage were compared using the chi-square test. A P value of less than 0.05 was considered significant. Results: A total of 138 patients who had cranial venous sinus thrombosis were included in the study. Seventy-three (52.9%) were women and the median age of subjects was 35 (interquartile range 22–47) years. Venous infarcts and haemorrhagic venous infarcts were noted in 20/138 (14.5%) and 62/138 (44.9%) cases, respectively. Subarachnoid haemorrhage was present in 15/138 (10.9%) cases and, in three cases, subarachnoid haemorrhage occurred in the absence of a venous infarct. Haemorrhagic venous infarcts were more prevalent ( P  = 0.021) among patients with subarachnoid haemorrhage (11/15) than in those without subarachnoid haemorrhage (51/123). Conclusion: In patients with cranial venous sinus thrombosis, subarachnoid haemorrhage can occur even in the absence of a haemorrhagic venous infarct. The recognition of cranial venous sinus thrombosis as the underlying cause of subarachnoid haemorrhage is important to avoid misdiagnosis and inappropriate management.